Efficiency Effects of Privatising Refuse Collection: Be careful and Alternatives present - E. Dijkgraaf; R. Gradus (Tinbergen Institute, 2011)
For refuse collection, we estimate the cost effects of different institutional modes using panel data for almost all Dutch municipalities between 1998 and 2010. The modes we consider are private contracts, intermunicipal cooperation, public provision and own collection. For private companies, the cost advantage is substantially smaller and non-significant if municipal fixed effects are included. The cost advantage of intermunicipal cooperation is larger in this case than that of privatisation. Moreover, if yearly mode dummies and mode duration are also included, we show that for 2004, 2005 and 2006 a large cost increase is visible for privatisation. Which mode offers the most cost-saving opportunity depends strongly on the year and the mode duration. For private contracts, the duration effects lead to lower costs; for municipal cooperation and public provision, there are extra costs to begin with, which disappear after 5 or 6 years.
urn:NBN:nl:ui:31-1871/38552
Keywords: D43; L33; R51; 330; Waste collection; private firms; contracting out; fixed effects